1977
DOI: 10.1159/000280112
|View full text |Cite
|
Sign up to set email alerts
|

Serum Proteins in Prostatic Cancer

Abstract: Preliminary studies of sera from prostatic cancer patients have indicated a reduction in the presence of suppressive (‘blocking’?) properties of in vitro parameters of cell-mediated immunologic responsiveness induced by a non-specific mitogen (phytohaemagglutinin) in association with a decrease in the level of α2-globulin and favourable clinical response following cryosurgery. The origin of the immunosuppressive factor(s) migrating on electrophoresis in the α2-globulin fraction of serum r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The earliest reports on immune modification after cryoablation described autoantibody production against ablated normal and tumor tissues in rabbits and monkeys, as well as in patients [41, 106–112, 114]. These antibodies were essentially IgG and IgM in the serum [41, 86, 114] and at the vicinity of the ablated lesion mainly IgG and IgA [115] appearing within two weeks after intervention [41, 86, 114].…”
Section: Cryoablationmentioning
confidence: 99%
See 1 more Smart Citation
“…The earliest reports on immune modification after cryoablation described autoantibody production against ablated normal and tumor tissues in rabbits and monkeys, as well as in patients [41, 106–112, 114]. These antibodies were essentially IgG and IgM in the serum [41, 86, 114] and at the vicinity of the ablated lesion mainly IgG and IgA [115] appearing within two weeks after intervention [41, 86, 114].…”
Section: Cryoablationmentioning
confidence: 99%
“…These antibodies were essentially IgG and IgM in the serum [41, 86, 114] and at the vicinity of the ablated lesion mainly IgG and IgA [115] appearing within two weeks after intervention [41, 86, 114]. In contrast, Müller and colleagues treated osteosarcoma in mice with cryoablation and found a decrease of tumor-binding antibodies [113].…”
Section: Cryoablationmentioning
confidence: 99%
“…Studies in patients with prostatic carcinoma have shown an immunological defect which depresses cellular immunity and accelerates progression of the disease This immunological defect also seems to be related to a serum factor [4,5]. Protein electrophoretic studies have shown that in such cases a,-globulin fraction, consisting of RNase as active component, increases in the serum [6,7]. The immunosuppressive effect of RNase is well known [S].…”
Section: Introductionmentioning
confidence: 99%